Developing a domain-specific risk management framework for music festivals in Malaysia - Ismail, Khairiah (2022)
A music festival is a well-known event that is organized all over the world. It has a significant impact not just on the host country but also on the host community. However, despite its positive impact, the music festival has also been seen as a negative event due to many risky incidents occurred. In Malaysia, music festivals are not widely organized compared to other countries due to the high rate of cancellation and rejection by the government authorities for several reasons, including permit revocation, accidents, or sensitive issues. Apart from that, the absence of a risk management plan for organizers to implement is a reason behind undesirable incidents at music festivals. Therefore, this study aimed to conduct an in-depth investigation of why music festivals in Malaysia are cancelled or rejected and why no action has been taken by associated stakeholders (e.g., government authorities and organizers). This investigation was driven by three research objectives: 1) to explore stakeholders’ views of Malaysian music festivals; 2) to explore their risk-taking behavior when participating in this event; and 3) to develop a risk management framework for music festivals in Malaysia. The issues revealed in this study correspond to practical gaps in the Malaysian event industry and are supported by relevant literature on risk in music festivals such as: the Event Management Body of Knowledge (EMBOK) established by O’Tolle (2008) and the Domain-Specific Risk-Taking (DOSPERT) behavior model developed by Blais and Weber (2002). The EMBOK model guided the first research question, which explored Malaysian music festivals in relation to EMBOK risk domains while DOSPERT theory guided the second research question, which investigated why stakeholders are eager to participate in music festivals despite knowing their risks and prior incidents. To answer the third research question, the combination of EMBOK and DOSPERT was utilized to develop a domain-specific risk management framework for music festivals in Malaysia. This study employed the qualitative method to interview 27 informants selected from attendees, organizers, and government authorities who have actively participated in Malaysian music festivals. In addition to semi-structured interviews, the researcher implemented documentary sources and went to two music festivals in Malaysia. The data were analyzed using both deductive and deductive approaches, following the EMBOK and DOSPERT theories outlined in the literature. Atlas.ti software was used to perform thematic analysis of the data to discover specific codes and themes that answer the research objectives. To conclude, the findings of this study are significant and relevant in filling the practical and theoretical gaps. The domain-specific risk management framework proposed by this study can be implemented by music festival organizers in Malaysia to avoid any unforeseen circumstances or incidents during their event. Apart from that, this framework provides a better understanding for the government authorities so they can address the unstandardized issue of approving and rejecting music festivals. Finally, this study recommends that attendees do not engage in any risky behavior before or during music festivals to prevent negative consequences.